2000
DOI: 10.1159/000045605
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Autonomic Neuropathy in Patients with Chronic Renal Failure on Hemodialysis

Abstract: To characterize uremic cardiac autonomic neuropathy, we measured plasma catecholamines, analyzed the 24-hour heart rate variability (HRV), and acquired serial images with 123I-metaiodobenzylguanidine (MIBG) in 44 patients with chronic renal failure on hemodialysis and in 14 controls. Time-domain measures were calculated using the Marquette HRV program. MIBG clearance rates from the heart and lung were evaluated on planar images, and the regional MIBG uptake in the left ventricular myocardium was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 39 publications
(62 reference statements)
4
26
1
Order By: Relevance
“…It seemed to be caused by impairment of the cardiovascular autonomic control characterized by withdrawal in parasympathetic modulation and predominance in sympathetic tone (28). As in previous studies (17)(18)(19)(20)(29)(30)(31)(32)(33), our results showed that stage 5 CKD patients exhibited a marked reduction in HRV indices relative to age-and sex-matched controls, indicating that sympathetic hyperactivity may play an important role in increasing the risk of CVD among ESRD patients.…”
Section: Discussionsupporting
confidence: 83%
“…It seemed to be caused by impairment of the cardiovascular autonomic control characterized by withdrawal in parasympathetic modulation and predominance in sympathetic tone (28). As in previous studies (17)(18)(19)(20)(29)(30)(31)(32)(33), our results showed that stage 5 CKD patients exhibited a marked reduction in HRV indices relative to age-and sex-matched controls, indicating that sympathetic hyperactivity may play an important role in increasing the risk of CVD among ESRD patients.…”
Section: Discussionsupporting
confidence: 83%
“…34 A reduction of HRV in ESRD patients has been demonstrated in some earlier reports, [19][20][21]35 whereas some other groups reported increased LF power. 36 This discrepancy may be related to clinical or methodological differences.…”
Section: Discussionmentioning
confidence: 81%
“…Earlier studies have reported that sympathetic nerve activity is increased in hemodialysis patients (15,26) and an elevated plasma NE level independently predicts mortality (27). Scaling exponent a 1 decreases with increased levels of circulating noradrenaline in healthy men (28) and increases with b-blocker therapy in Data are n (%) for categorical data, median (interquartile range) for continuous normally distributed data, and mean 6 SD for those not normally distributed.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it also increases with atropine and decreases with vagal activation (28,31). Because vagal activity is generally reduced in hemodialysis patients (15)(16)(17), those with and without sympathetic overactivity might be better discriminated by scaling exponent a 1 than by the measures simply reflecting vagal modulation. This study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation